A CHLORINE PRODUCTION IN A CHLORINE PLANT SYSTEM USING AC AND DC CURRENT AT THE PANGKALAN SUSU - M Yuda Prahmana Putra; Solly Aryza; Zulkarnain Lubis (Jurnal Scientia, 2023)
In a Steam Power Plant system. there are problems in the production process, requiring a cooling system that is used for work efficiency, namely circulation (steam recycling), and cooling the motor and pump using the natural temperature of sea water. In this research, we discuss the chlorine cooling system, so we need a system that can prevent marine biota from entering the cooling water circulation system, namely by providing high levels of chlorine liquid to the sea water intake (intake), which can expel biota . , and kill the moss. Therefore, it is necessary to create a Chlorination System Simulation at Steam Power Plants (PLTU), the aim of which is to maintain the efficiency of the system so that it works better.